Jen the hen - Hawkins, Colin; Hawkins, Jacqui (New York : G.P. Putnam's Sons, 1985)
Jen the hen sends a message to Ken and Ben via Wren to meet at ten in the glen.
Booklist
School Library Journal
1.0
K-3
Keywords: Toy and movable books -- Specimens; Chickens -- Fiction; Stories in rhyme; Toy and movable books; Chickens -- Fiction; Stories in rhyme